Propuesta de mejoramiento basado en el balanced scorecard para el proyecto información a las comunidades de una institución perteneciente al sector petrolero (2018)
Within the framework of this work, we analyze the weaknesses of a pioneering pedagogy project at an oil and gas industry institution in Colombia, which is responsible for imparting knowledge through numerous training sessions and seminars dictated by experts from oil and gas sector, in order to contribute to professional training of industry engineers and educate the general public that wants to know more about it.